Deindustrialization and economic policies in the Pacific Alliance countries: 1986-2009 (LACCEI, 2024)
The objective of the study was to analyze the premature deindustrialization experienced by the countries of the Pacific Alliance between 1986 -2009. The research was applied, non-experimental and quantitative. In the hypothesis test, panel data regression techniques have been used with ordinary least squares and fixed effects approaches Statistical information has been obtained from the databases of: GGDC 10-Sector, UNCTAD-Statistics, WDI-BM, CEPALSTAT, and BID-WP-346. The result of the estimation of regression equations confirms the hypothesis on the decrease in manufacturing employment by -0.44%, -0.78%, -0.05% and -1.08% as a result of the 1% advance in financial and tax reforms, privatizations and labor flexibility respectively Likewise, manufacturing value added has been negatively affected by -0.63%, -0.03%, -0.26% and -0.02% due to the 1% advance in trade liberalization, financial reform, tax reform and privatizations respectively. The statistical value of R2 and F of both equations are statistically significant.